Short Communication: Exploration of bidara laut (Strychnos lucida) parent trees in Gunung Tunak Ecotourism Park, West Nusa Tenggara, Indonesia - ALI SETYAYUDI; KRISNAWATI KRISNAWATI; RYKE NANDINI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Setyayudi A, Krisnawati, Nandini R. 2019. Short Communication: Exploration of bidara laut (Strychnos lucida) parent trees in Gunung Tunak Ecotourism Park, West Nusa Tenggara, Indonesia. Biodiversitas 20: 374-378. Bidara laut (Strychnos lucida R. Brown) is one of the widely used medicinal plants. There is a bidara laut wood processing industry in West Nusa Tenggara that produces drinking cups called ‘health cups’ utilizing bidara laut. All raw materials used for the production of health cups are, however, obtained from bidara laut stands in forest areas, which may cause the extinction of this medicinal plant species if the highly intensive raw material harvesting in the forest is not supported with cultivation of this plant species. To preserve this plant species, the Institute for Research and Development of Non-Timber Forest Products Technology (NTFP-RDI) has carried out breeding activities by developing a collection garden of this species from the populations of Bali and West Nusa Tenggara (Lombok and Sumbawa Islands). The initial step carried out was the exploration of the parent trees followed by collection of generative materials (seeds) and nurseries. Exploration of bidara laut parent trees on Lombok Island was carried out in Gunung Tunak Ecotourism Park using a purposive sampling method, followed by collection of fruits to obtain seed propagating materials for establishment of seedling nurseries. Twenty-five parent trees were identified with average height of nine m, stem diameter of 24 cm and stem straightness scales of 1-3. The average seed produced was 413 seeds tree-1. Three parent trees were selected based on the highest seed germination rates, namely parent trees number 6, 14 and 20. This result provides useful information for the next bidara laut breeding activities.